An Investigation into the Efficiency of the Modified Sawdust and Rice Bran in Treating the Polluted Aqueous Solutions with Cr (VI) - Zahra Ameri; Mehran Hoodaji; Majid Rajaie; Mitra Ataabadi (مهندسی منابع آب, 2023)
Abstract Introduction: This study investigated the possibility and efficiency of absorbing Cr (VI) ions from the polluted water by employing the chemically modified natural adsorbents of sawdust and rice bran. For each adsorbent three chemical modifications were considered (i.e., acid, biochar and alkali) and the impacts of various adsorbents’ pH values, dosages, concentrations and contact times were studied. Methods: The colorimetric method using UV/VIS spectrophotometer was used for Cr determination. Moreover, for analyzing the characteristics of the modified adsorbents, the “Scanning Electron Microscope” and “Fourier-Transform Infrared Spectroscopy” were utilized. Findings: It was found that the acid sawdust and rice bran had functioned better than the other chemical modifications. In fact, the highest efficiency of Cr (IV) adsorption from the polluted aqueous solutions occurred at pH 2, contact-time of 100 minutes, Cr concentration of 50 mg/L and adsorbent dosage of 2 g/L by acid sawdust (96.73%), biochar sawdust (95.60%), acid rice bran (94.50%), biochar rice bran (94.27%), alkali sawdust (92.36%) and alkali rice bran (88.6%), respectively. The adsorption kinetics was agreeably suited to the equations of pseudo second order while the Freundlich isotherm equation was also suitably expounded the study’s findings. The findings depicted that the acid and biochar sawdust and rice bran better than the alkali ones, performed remarkably in the remediation of the wastewater. This would result in the wastewater treatment and its reuse for industrial, agricultural and environmental purposes.